2014
DOI: 10.1037/spq0000042
|View full text |Cite
|
Sign up to set email alerts
|

The influence of student characteristics on the dependability of behavioral observation data.

Abstract: Although generalizability theory has been used increasingly in recent years to investigate the dependability of behavioral estimates, many of these studies have relied on use of general education populations as opposed to those students who are most likely to be referred for assessment due to problematic classroom behavior (e.g., inattention, disruption). The current study investigated the degree to which differences exist in terms of the magnitude of both variance component estimates and dependability coeffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Although some of the variability in regard to the number of observations needed to obtain reliable/dependable data are likely attributable to differences in the time-sampling method utilized as well as the length of observation, it is important to note that the characteristics of the students varied across studies as well. Prior research has highlighted the fact that a greater number of observations may be needed to dependably assess the behavior of those students referred for behavioral concerns than their typical peers (Briesch, Volpe, & Ferguson, 2013). Whereas all of the students in the study by Volpe et al (2009) had been referred for concerns related to their behavioral-emotional functioning, the other three studies focused on students within general education classrooms.…”
Section: Discussionmentioning
confidence: 99%
“…Although some of the variability in regard to the number of observations needed to obtain reliable/dependable data are likely attributable to differences in the time-sampling method utilized as well as the length of observation, it is important to note that the characteristics of the students varied across studies as well. Prior research has highlighted the fact that a greater number of observations may be needed to dependably assess the behavior of those students referred for behavioral concerns than their typical peers (Briesch, Volpe, & Ferguson, 2013). Whereas all of the students in the study by Volpe et al (2009) had been referred for concerns related to their behavioral-emotional functioning, the other three studies focused on students within general education classrooms.…”
Section: Discussionmentioning
confidence: 99%
“…Teacher rating scales that represent constructs such as hyperactivity, inattention, and aggression (e.g., Behavior Assessment System for Children–Third Edition [BASC-3; Reynolds & Kamphaus, 2015 ], Sutter–Eyberg Student Behavior Inventory, Revised [SESBI-R; Eyberg & Pincus, 1999 ]) are another option. A strength of rating scales is strong evidence for reliability and validity of many scales (e.g., SESBI-R: Querido & Eyberg, 2003 ), while an important limitation is that they represent a teacher’s perspective and thus may be biased (Briesch et al, 2018 ). Another approach is direct behavior ratings (DBR) of specific target behaviors over brief time periods, such as a classroom activity.…”
Section: Introductionmentioning
confidence: 99%
“…SDOs are typically conducted over 10–30 min and can quantify behavior in terms of features such as frequency, duration, and time sampling interval recording (e.g., partial interval, in which the behavior is coded if it occurs at least once in the interval; whole interval, in which the behavior is coded only if it occurs for the duration of the interval; and momentary time sampling, in which the behavior is coded if it occurs at a designated point in the interval). While training to use SDOs can be time consuming and SDOs only capture a brief sample of behavior, SDO data are more objective than teacher ratings, DBRs, or narrative observations (Briesch et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies found that DBR generates reliable scores by reflecting a large amount of variance explained by the actual student's behavior (e.g., Owens and Evans 2017). However, results from different raters across multiple time points indicate that different persons rate the same behavior differently and that students behave differently across multiple occasions (e.g., Briesch et al 2010;Volpe and Briesch 2012;Briesch et al 2014). Therefore, multiple measurement points are necessary to provide a stable score that still is interpretable.…”
Section: Introductionmentioning
confidence: 99%